A simple infill frame with macro element masonry model for the in-plane performance of infill walls. (August 2022) - Islam, Mohammad Tariqul; Noor-E-Khuda, Sarkar; Saito, Taiki
Abstract: This paper assesses the factors those influence the in-plane structural behavior of masonry infill frames when exposed to seismic loading. The assessment is carried out using an infill frame with macro-element masonry (IFM 2 ) model developed using an open-source computer program, STERA 3D. The frame and the masonry infill of the IFM 2 model are simulated using the beam and column elements, and the masonry macro-elements, respectively, which are discretized through appropriate combinations of nonlinear bending spring and shear spring, and axial spring and shear spring, respectively. The model was validated against the test results of three bare frames and seven masonry infill reinforced concrete (RC) and steel frames reported in the literature and the results reflect a good match in the datasets. Besides, a series of parametric studies were performed to check the influence of column size, column reinforcement ratio, brick and mortar strength, and aspect ratio on the lateral load capacity, as well as the stiffness and ultimate load of the infill RC frames. The results match well with the predictions of the strut models available in the literature and it is found that the size of the column elements of the frame, as well as the compressive strength of the brick, are the dominating factors that influence the in-plane capacity of the infill RC frames.